Deklinasi adjektiva Bahasa Jerman dan penggunaannya oleh Mahasiswa Jurusan Sastra Jerman Universitas Negeri Malang - Bela, Nindi Sania; Hidayat, Edy (2021)
141Seminar Nasional Pembelajaran Bahasa dan Sastra (SELASAR) 5 ISSN: 2541-349X PROCEEDINGS DEKLINASI ADJEKTIVA BAHASA JERMAN DAN PENGGUNAANNYA OLEH MAHASISWA JURUSAN SASTRA JERMAN UNIVERSITAS NEGERI MALANG Nindi Sania Bela (1), Dr. Edy Hidayat, S.Pd., M.Hum. (2) Universitas Negeri Malang 1 Universitas Negeri Malang 2 Nindisaniabela@gmail.com Abstrak: One of the uniqueness of German language is the use of adjectives that can be attributed and predictive. as an attribute, German adjectives undergo morphological structural changes, i.e. the addition of endungs or suffixes adapted to Numerus, Kasus, and Genus of their nouns. The change is known as declination. The phrase ein schönes Auto in the sentence Er hat ein schönes Auto is an example of adjectives as attributes that undergo a declination process. In the use of declination adjectives by students of the German Department of Literature there are still various errors. This study aims to describe the use of German adjective declination by students in Aufsatz II courses. The research design used is descriptive qualitative. The data source in this study were 2017 Offering A students of German Literature Departement, State University of Malang, who had taken the Aufsatz II course with a total of 25 students. The data in this study were sentences in student essays in the Aufsatz II course which contained errors in the use of adjectives declination. Based on the results of data analysis, it was found that there were errors made by students in using adjectives declination. The forms of errors are (1) Error in using adjective declination based on Genus, (2) Error in using adjective declination based on Numerus, (3) Error in using adjective declination based on Kasus, and (4) Error in using declination on superlative adjective. From the four errors, students made the most errors in using the adjective declination based on Genus, approximately 17 errors and in the second place is errors in using the adjective declination based on Kasus, approximately 7 errors.